What narcissism means to me - Hoagland, Tony (Graywolf Press, 2003)
From the Publisher: In What Narcissism Means to Me, award-winning poet Tony Hoagland levels his particular brand of acute irony not only on the personal life, but also on some provinces of American culture. In playful narratives, lyrical outbursts, and overheard conversations, Hoagland cruises the milieu, exploring the spiritual vacancies of American satisfaction. With humor, rich tonal complexity, and aggressive moral intelligence, these poems bring pity to our folly and celebrate our resilience.